Design of pH-Responsive Nanomaterials Based on the Tumor Microenvironment - Liu Y; Si L; Jiang Y; Jiang S; Zhang X; Li S; Chen J; Hu J (International Journal of Nanomedicine)
Yunheng Liu,1,* Longqing Si,1,* Yuxuan Jiang,1,* Shaojing Jiang,2 Xiaokang Zhang,1 Song Li,1 Jing Chen,1 Jinghui Hu2 1School of Pharmacy, The Key Laboratory of Prescription Effect and Clinical Evaluation of State Administration of Traditional Chinese Medicine of China, Binzhou Medical University, Yantai, 264003, People’s Republic of China; 2Yantai Engineering Research Center for Digital Technology of Stomatology, Characteristic Laboratories of Colleges and Universities in Shandong Province for Digital Stomatology, Institute of Stomatology, Binzhou Medical University, Yantai, 264003, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jing Chen, School of Pharmacy, The Key Laboratory of Prescription Effect and Clinical Evaluation of State Administration of Traditional Chinese Medicine of China, Binzhou Medical University, Yantai, 264003, People’s Republic of China, Email chenjingbyyxy@163.com Jinghui Hu, Yantai Engineering Research Center for Digital Technology of Stomatology, Characteristic Laboratories of Colleges and Universities in Shandong Province for Digital Stomatology, Institute of Stomatology, Binzhou Medical University, Yantai, 264003, People’s Republic of China, Email bykfhjh@163.comAbstract: The metabolic activity of tumor cells leads to the acidification of the surrounding microenvironment, which provides new strategies for the application of nanotechnology in cancer therapy. Researchers have developed various types of pH-responsive nanomaterials based on the tumor acidic microenvironment. This review provides an in-depth discussion on the design mechanisms, drug-loading strategies, and application pathways of tumor acidic microenvironment-responsive nanodrug delivery systems. These materials trigger drug release upon reaching the tumor microenvironment, enhancing therapeutic targeting and reducing toxicity to healthy cells. pH-responsive nanomaterials include organic nanomaterials, inorganic nanomaterials, and composite nanomaterials. Additionally, this review outlines the drug-loading strategies, application prospects, and challenges of pH-responsive nanomaterials, aiming to promote the development and clinical translation of this field.Keywords: tumor microenvironment, pH response, nanocarriers, drug-loading strategies, drug delivery system